Comparative study of the endocrine functions in Norplant vs Depoprovera acceptors - Mochamad Anwar, Mochamad Anwar (Universitas Gadjah Mada, 1994)
The steroidal contraceptive agents are highly predictable in preventing pregnancy, however, all currently used synthetic progestogens have certain potential side effects. These side effects may be due to either the direct actions of the synthetic steroids or the indirect actions through the womens own endocrine system.The objective of the study is to evaluate potential alterations of the endocrine functions in women using Norplant compared to injectable contraceptive method.The study was conducted in a cohort study by recruiting 25 women in each group receiving either Norplant or Depoprovera contraceptive method voluntarily. Six months after entering the study 10 ml of blood was taken from the cubits] vein and follicle stimulating hormone (FSH) , luteini zing hormone (LH), prolactine (PRL), progesterone (P), oestradiol (E2), total testosterone (r), free testosterone (FT) and sex hormone binding globulin (SHBG) were measured using radioimmunoassay.The mean of SHBG level in Norplant (29.44 ÃÂ± 9.85 nmol/l) is statistically, lower (p421.001) compared to Depoprovera acceptors (50.64 ÃÂ± 21.29 nmol/l), however, they were still in the normal range. The means of total testosterone and free testosterone level were higher in Norplant group, however, they were not statistically different (p = 0,391 and 0.182 respectively). No androgenicity symptoms were clinically found in both groups. Either Norplant or Depoprovera lowering the secretion of progestogen and oestrogen, indicated that the alterations of endocrine function occured more frequently in the level of target organ (ovary) rather than in the level of hypophysis or hypothalamus. These findings were also confirmed by the mean levels of FSH, LH and prolactine which were also in the normal range.It is concluded, that there were no potential alterations of the endocrine functions in women using either Norplant or Deprovera especially in androgenicity. The influence of both progestogen contraceptive methods were greater on the level of target organ.Key words : contraception-Norplant-Depoprovera -radioimmuno assay-blood